A STUDY ON WORK LIFE BALANCE OF WOMEN EMPLOYEES IN IT SECTOR - Balamurugan, G.; Sreeleka, M. (International Journal of Engineering Technologies and Management Research, 2020)
Work life balance of women employees plays the major role because they have to manage their personal life for their good quality of life. The employee’s satisfaction is based on the employee to be happy and deliver the level best. Even in the Worst scenario the employee is very loyal to their organization because of the employee Satisfaction. The quality of life is based on the professional life of each and every women employee who are coming forward to support to their family. The problem of the women employee’s face is health condition, Pregnancy discrimination, Sexual harassment, no equal pay, etc. This paper says that how the women employees are balanced and Satisfied in IT sector and the factors that affect the work life balance of women employees are working hours, Job satisfaction, working condition, etc. and find out the women employee job satisfaction were analyzed by using statistical method that is Chi-square and Correlation test.